Every Man out of His Humour - Jonson, Ben, 1573?-1637 (Salt Lake City, UT : Project Gutenberg, 2003)
"Every Man out of His Humour" by Ben Jonson is a satirical comedy play written in 1599. A sequel to Jonson's earlier success "Every Man in His Humour," this play satirizes social ambition and literary rivalries of Elizabethan London. The work features characters that mock real-world figures and playwrights, including pointed references to the theatrical disputes of the era. Though less successful on stage than its predecessor, the play was published three times in 1600 and includes notable allusions to Shakespeare's works. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Every_Man_out_of_His_Humour
Release date is 2003-01-01
Produced by Sue Asscher, Amy E Zelmer, and David Widger
Keywords: English drama (Comedy)